Preliminary Study on Antifungal Mechanism of Aqueous Extract of Cnidium monnieri Against Trichophyton rubrum - Yanyun, Cao; Ying, Tang; Wei, Kong; Hua, Fang; Haijun, Zhu; Ping, Zheng; Shunming, Xu; Jian, Wan (Frontiers in Microbiology, 2021)
Trichoderma rubrum (T. rubrum) is one of important pathogens because it is the cause of most dermatomycosis. The treatment of Trichophyton rubrum infection is time- consuming and very expensive, it is easy for the infections to reoccur, leading to therapeutic failures, persistence and chronic infection. These issues have inspired researchers to study natural alternative therapies instead. Cnidium monnieri(L.), as a kind of traditional Chinese medicine, has a variety of pharmacological activities and a wide range of applications, so it has a high potential for researching and economic value. We detected the effect of aqueous extract of Cnidium monnieri(L.) on the activity of T. rubrum by Cell Count Kit-8 assay (CCK-8),and found that 128μg/mL and 256μg/mL aqueous extracts of Cnidium monnieri (L.) co-cultured with T. rubrum for 24 h showed the inhibitory effect on T. rubrum. The results of SEM and TEM confirmed that aqueous extract of Cnidium monnieri (L.) damaged the T.rubrum. At the same time, mass spectrometry screening with T. rubrum before and after the treatment of 256μg/mL aqueous extracts of Cnidium monnieri (L.) showed that 966 differentially expressed proteins were detected, including 524 upregulated differentially expressed genes (DEGs) and 442 downregulated DEGs. The most significantly downregulated protein was chitin synthase (CHS); and the results of qRT-PCR and Western-blot demonstrated that expression level of CHS was down regulated in the 256 μg/mL group compared with control group. The study showed that the aqueous extract of Cnidium monnieri (L.) could destroy the morphology of mycelial and the internal structure of T. rubrum and it could inhibit the growth of T. rubrum. The antifungal effect of aqueous extract of Cnidium monnieri (L.) may be related to the downregulation of the expression of CHS in T. rubrum, and CHS may be one of the potential targets of its antifungal mechanism. We concluded that aqueous extract from Cnidium monnieri (L.) may be a potential candidate for antifungal agents.